(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article examines the importance of learner-centered approaches in the context of Teaching English as a Foreign Language (TEFL). Unlike traditional teacher-centered models, learner-centered methods focus on student engagement, autonomy, and interaction. Drawing on qualitative research and practical classroom experiences, the study highlights how strategies such as task-based learning, group work, and the use of authentic materials can enhance language acquisition and motivation. The findings suggest that incorporating learner-centered pedagogy in EFL classrooms leads to improved communication skills and greater learner satisfaction, while also presenting new challenges for educators in terms of training and resources.